Solve -2(4y + 6) = 52.

Question

Asked 5/5/2015 9:22:43 AM

Updated 5/14/2015 5:55:09 AM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/14/2015 5:53:24 AM]

migzptz|Points 7632|

Question

Asked 5/5/2015 9:22:43 AM

Updated 5/14/2015 5:55:09 AM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/14/2015 5:53:24 AM]

Rating

3

All of the following are equivalent except -4x - 8.

-4(x - 2) = 8 - 4x = -4x + 8

-4(x - 2) = 8 - 4x = -4x + 8

Added 5/14/2015 5:53:21 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/14/2015 5:58:25 AM]

3

-2(4y + 6) = 52

-8y - 12 = 52

-8y = 52 + 12 = 64

y = 64/-8 = -8

-8y - 12 = 52

-8y = 52 + 12 = 64

y = 64/-8 = -8

Added 5/14/2015 5:53:59 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/14/2015 5:58:33 AM]

3

The solution to 4x + 7 - 9 = -14 is -3.

4x + 7 - 9 = -14

4x = -14 + 9 - 7 = -12

x = -12/4 = -3

4x + 7 - 9 = -14

4x = -14 + 9 - 7 = -12

x = -12/4 = -3

Added 5/14/2015 5:55:09 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/14/2015 5:58:48 AM]

Which of the following algebraic equations could represent the sentence, "The quotient of a number and 9 is three"?
x - 9 = 3
x + 9 = 3
= 3
9x = 3

Question

Not Answered

Updated 2/2/2016 11:24:45 PM

2 Answers/Comments

graph of y = -2x + 4. User: value of -7 + (-9) + 11 + 8.

Question

Updated 5/14/2015 1:06:15 PM

1 Answer/Comment

What is the value of -5.872 + (-5.1) ÷ 1.5?
-9.272
-2.472
-7.315
0.515

Question

Not Answered

Updated 5/1/2015 9:21:18 AM

1 Answer/Comment

Solve -3n + 4 > -8.

Question

Updated 5/1/2015 11:05:12 AM

1 Answer/Comment

-3n + 4 > -8;

-3n > -8 - 4;

-3n > -12;

n < -12/-3;

n < 4

-3n > -8 - 4;

-3n > -12;

n < -12/-3;

n < 4

Added 5/1/2015 11:05:12 AM

This answer has been confirmed as correct and helpful.

In which of the following would you divide both sides of the equation by b?
Solve for b.
Solve a - b = c for b.
Solve ab = c for a.
Solve a + b = c for b.

Question

Not Answered

Updated 5/5/2015 11:26:15 AM

1 Answer/Comment

In "Solve ab = c for a" would you divide both sides of the equation by b.

Added 5/5/2015 11:26:15 AM

This answer has been confirmed as correct and helpful.

31,888,530

questions answered

There are no comments.